Operating Cash Flow On Financial Distress (Study On Companies Listed On The Indonesia Stock Exchange (Idx) For The Period Of 2018-2021 In The Transportation And Logistics Sector Of Service Companies) - Suryani, Aurelia Putri; Aminah, Wiwin (UNIVERSITAS PAKUAN, 2019)
Bankruptcy of a company will begin with financial difficulties. Companies that are unable to compete in the world economy will certainly have financial difficulties and eventually have bankruptcy which will be reflected in the company’s financial performance. The objective of this research is to identify the effect of profitability, operating cash flow and sales growth on financial distress. The object of this study are service companies in the transportation and logistic sector that are listed on the IDX in 2018-2021. This research used purposive sampling to collect the samples. Nineteen samples for a 4 years research period were collected, resulting in a total 76 samples. The method of this research used logistic regression analysis and testing using Eviews 12. The result in this research showed that simultaneously profitability, operating cash flow and sales growth have an effect on financial distress. Partially, profitability and sales growth have no effect on financial distress, on the other hand operating cash flow has a negative effect on financial distress on service companies in the transportation and logistic sector that are listed on the IDX in 2018-2021.